DETERMINATION OF INTERESTS IN BUYING SAMSUNG BRAND SMARTPHONE IN ONLINE LEARNING IN THE ERA OF COVID-19 - Ramdani Bayu Putra; Elfiswandi Elfiswandi; Sitti Rizki Mulyani; Muhammad Ridwan; Hasmaynelis Fitri (Universitas Padjadjaran, 2023)
The Covid-19 pandemic has changed the order of all activities of human life, including in the field of education. The use of information system technology is very helpful in online learning, from elementary school to college level. Smartphones are intelligent communication tools that have many features to support online learning. The high use of smartphones has an impact on customer buying interest, especially since the Covid 19 pandemic. This study tries to analyze the interest in buying Samsung brand smartphones in online learning. The sample of this research is 98 students of Putra Indonesia University YPTK Padang. This research model is a structural equation modelling (SEM) model with SmartPLS 3 analysis tool. The results show that buying interest in Samsung brand smartphones is influenced by celebrity endorsers and brand image factors. The research findings state that the contribution of figures in the form of celebrities and brand image is a determining factor in buying Samsung brand smartphones. While the mediating effect of brand image cannot strengthen the influence of celebrity endorsers on the purchase intention of Samsung brand smartphones. This means that consumer buying interest in Samsung brand smartphones does not always pay attention to the brand image, but sometimes it is more to the celebrity endorser factor. This finding recommends that companies can further maintain and strengthen the celebrity endorser factor and be able to improve the quality of their product brand image so that consumer buying interest becomes higher in marketing their products.